2020
DOI: 10.1097/md.0000000000023302
|View full text |Cite
|
Sign up to set email alerts
|

Monokine induced by gamma interferon for detecting pulmonary tuberculosis

Abstract: Backgrounds: Pulmonary tuberculosis (PTB) is an oldest-known and most formidable disease. The standard microbiology culture is time-wasting. Monokine induced by gamma interferon (MIG) has been reported as a new biomarker to auxiliarily detect PTB. In our study, we used meta-analysis to assess the diagnostic value of MIG for PTB. Methods: PubMed, Embase, Web of Science, and Cochrane Library were searched for relative records up to April 2, 2020. The pool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…MIG levels are also high in patients with tuberculosis. A systematic review and meta-analysis on the predictive accuracy of MIG in antigen-stimulated and unstimulated supernatants among patients with culture positive tuberculosis found that pooled sensitivity and specificity were both 84% [34]. A prior study investigated the diagnostic accuracy of IP-10/MIG-values for TB-infection in antigen-stimulated QFT tubes derived from healthcare workers classified as those without TB-infection (defined by a QFT result <0.1 IU/mL and TST result <10mm), undetermined TB-infection (defined by a QFT result between 0.1 and 0.35 IU/mL and/or a TST >10mm), and with TB-infection (QFT result ≥0.35 IU/mL) [35].…”
Section: Discussionmentioning
confidence: 99%
“…MIG levels are also high in patients with tuberculosis. A systematic review and meta-analysis on the predictive accuracy of MIG in antigen-stimulated and unstimulated supernatants among patients with culture positive tuberculosis found that pooled sensitivity and specificity were both 84% [34]. A prior study investigated the diagnostic accuracy of IP-10/MIG-values for TB-infection in antigen-stimulated QFT tubes derived from healthcare workers classified as those without TB-infection (defined by a QFT result <0.1 IU/mL and TST result <10mm), undetermined TB-infection (defined by a QFT result between 0.1 and 0.35 IU/mL and/or a TST >10mm), and with TB-infection (QFT result ≥0.35 IU/mL) [35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified MIG as a potential diagnostic tool for TB infection ( 9 , 27 , 28 ). A systematic review and meta-analysis evaluating the predictive accuracy of MIG found pooled sensitivity and specificity both to be 84% among patients with culture-positive TB ( 29 ). Moreover, a study demonstrated that MIG outperformed IFN-γ in diagnosing active TB based on ROC analysis ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…MIG and IP-10 level decrease has also been associated with response to TB therapy [21] and lateral flow assays employing IP-10 as readout marker are currently under development, even if little information is available on their performance [2]. Furthermore, both MIG and IP-10 have been evaluated as possible biomarkers to discriminate between active TB and TB infection [22][23][24], and agonist and antagonist forms of IP-10 have been identified both in blood and urine of people with active TB [25,26].…”
mentioning
confidence: 99%